DNA Synthesis by Primer Exchange Reaction Cascades. (24th January 2018) - Hollenstein, Marcel
Abstract : Swap and extend : The autonomous synthesis of single‐stranded DNA molecules of arbitrary size and sequence composition can easily be achieved by primer exchange reaction (PER) cascades, in which the sequential polymerase‐mediated extension of DNA primers is guided by catalytic hairpins. This highlight illustrates the potential of this method for applications in DNA nanotechnology.